Pemanfaatan Educaplay sebagai Media Literasi Budaya di Sekolah Dasar - Della Khoirunnisak; Nor Lathifatur Rohmah; Febrina Eka Zunita; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Advances in information and communication technology have had a significant impact on the world of education, especially in increasing cultural literacy in elementary schools. Cultural literacy is the ability to understand and appreciate cultural norms, values ​​and diversity, which is very important in the era of globalization. One potential technology-based learning media is Educaplay, this interactive platform provides various interesting learning features. This research aims to analyze the use of Educaplay as a cultural literacy medium through the Systematic Literature Review (SLR) method. The research results show that Educaplay is able to increase students' interest and understanding of local culture through an interactive, flexible and contextual learning approach. This media also strengthens students' digital skills and encourages attitudes of tolerance and respect for cultural diversity. These findings underline the importance of integrating technology in cultural learning to create a generation that is culturally literate and globally competitive.